Bus drivers' perceptions of organisational justice & safety - Johnson, Craig (My University, 2015)
The number of safety incidents that occur on South African roads every day is a cause for great concern. The question of who is responsible for these incidents often arises, with blame often falling on the perceived ‘perpetrator’ of the safety incident. This may, however, not be the most appropriate approach to safety. This research identified bus drivers’ perceptions of organisational justice and analysed how these impacted on their safety attitudes and behaviours, using Reason’s Swiss Cheese Model and a Systems Theory model. Fourteen bus drivers participated in semi-structured interviews. Various themes arose from the research. These include Attitude towards safety, Relationship between drivers and management, Drivers satisfaction with the organisation, and Justice and Fairness. The results revealed that bus drivers’ perceptions of organisational justice are linked to their attitudes and behaviours towards safety.
A research report submitted in partial fulfilment of the requirements for the degree of Masters in Organisational Psychology in the Faculty of Humanities, University of Witwatersrand, Johannesburg February 2015